2022
DOI: 10.1111/cen.14700
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of a cohort of 271 patients with lung metastases from differentiated thyroid carcinoma

Abstract: Context Lung is the most common site of distant metastases from differentiated thyroid carcinoma (DTC). Objective To investigate the outcomes of a cohort of patients with DTC and lung metastases (LM). Methods A retrospective analysis of a cohort of 271 patients with LM was performed. Results The female‐to‐male ratio was 1:1 and the median follow‐up time was 5.9 (1.1–38.4) years. Papillary thyroid carcinoma (PTC) was the most frequent type (83.4%), mainly the classic variant, followed by follicular thyroid carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The overall prognosis for patients with DTC is favorable, while patients with distant metastases have a significantly poorer prognosis [ 7 , 8 ]. The lung is the most commonly affected site of distant metastases for DTC metastases, with an incidence rate of 2–20% [ 9 , 10 ]. Indeed, research indicated a higher incidence of lung metastasis compared to other organs in thyroid cancer patients with distant metastasis [ 11 , 12 , 13 ], likely due to the lungs’ extensive vascularization and tumor-friendly microenvironment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall prognosis for patients with DTC is favorable, while patients with distant metastases have a significantly poorer prognosis [ 7 , 8 ]. The lung is the most commonly affected site of distant metastases for DTC metastases, with an incidence rate of 2–20% [ 9 , 10 ]. Indeed, research indicated a higher incidence of lung metastasis compared to other organs in thyroid cancer patients with distant metastasis [ 11 , 12 , 13 ], likely due to the lungs’ extensive vascularization and tumor-friendly microenvironment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research indicated a higher incidence of lung metastasis compared to other organs in thyroid cancer patients with distant metastasis [ 11 , 12 , 13 ], likely due to the lungs’ extensive vascularization and tumor-friendly microenvironment [ 14 ]. Of those with lung metastases, 50% of patients die within 10 years [ 9 , 15 , 16 ]. Several factors, including age, serum thyroglobulin levels, cumulative dose of radioiodine therapy (RAI), and tumor size, have been shown to influence the prognosis of patients with DTC correlated with pulmonary metastases [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of PTC is generally good, with a 10-year survival rate of 80%–95% [ 9 ]. However, middle-aged PTC is prone to local lymphatic metastasis and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%